2010
DOI: 10.1007/s12012-010-9081-z
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol and Its Metabolites Induce Histone Lysine 9 Acetylation and an Alteration of the Expression of Heart Development-Related Genes in Cardiac Progenitor Cells

Abstract: Alcohol exposure during pregnancy may cause congenital heart disease (CHD), but the underlying mechanisms are not clear. Recent evidence suggests that ethanol and its metabolites can selectively increase histone H3 acetylation at lysine 9 (H3AcK9) residue in rat hepatocytes. This may be a mechanism by which ethanol alters gene expression. The goal of current study is to investigate the effect of ethanol and its metabolites on H3AcK9 acetylation and the mRNA expression of heart development-related genes (GATA4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…The cells were divided into five groups: alcohol; curcumin; alcohol + curcumin; DMSO; and control. From our previous studies [14, 18], we found that 200 mM alcohol was an effective concentration resulting in hyperacetylation of cardiac progenitor cells, and 25 μM curcumin could completely reversed the hyperacetylation induced by alcohol (200 mM). So we used 200 mM alcohol and 25 μM curcumin (SIGMA, USA) to intervene our cells for 24 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were divided into five groups: alcohol; curcumin; alcohol + curcumin; DMSO; and control. From our previous studies [14, 18], we found that 200 mM alcohol was an effective concentration resulting in hyperacetylation of cardiac progenitor cells, and 25 μM curcumin could completely reversed the hyperacetylation induced by alcohol (200 mM). So we used 200 mM alcohol and 25 μM curcumin (SIGMA, USA) to intervene our cells for 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…Acetylation of histone generated by histone acetyltransferases (HATs) can neutralize the positive charges between histone and DNA allowing the binding of transcription factors to DNA, and consequently advances gene transcription [13, 14]. In addition, studies have also revealed that alcohol exposure can lead to hyperacetylation of histone H3K9 [1517], an event believed to be associated with abnormal heart development [14, 1821]. H3K9 plays a critical role in cell cycle progression and apoptosis [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Both genetics and epigenetics play a part in regulating the expression of Gata4 and alterations that lead to uncontrolled expression of Gata4 could affect normal development of the heart. We have demonstrated that high consumption of alcohol or its metabolites can induce histone hyperacetylation that leads to over-expression of Gata4 [12], [13]. However, it is not clear whether alcohol exposure increases myocardial histone acetylation or Gata4 over-expression in developing hearts.…”
Section: Introductionmentioning
confidence: 93%
“…Under ethanol exposure, it was found that heart development was significantly affected, and H3 acetylation ensued. The effect was dose dependent, leading to greater gene expression changes in higher ethanol doses (Zhong et al, 2010). In fetal neuronal stem cell neurospheres, ethanol was observed to remove histone methylation marks from promoters (either H3K4me3 and H3K27me3, or both) across 20 candidate genes playing roles in processes such as the regulation of neural stem cell biology, and neural patterning (Veazey et al, 2013).…”
Section: Fetal Alcohol Exposure Causes Epigenetic Changes Critical Tomentioning
confidence: 99%